EXPLORING THE EFFECTIVENESS OF PERFORMANCE APPRAISAL IN - Parab, Mithila (2008)

(untitled)
This dissertation seeks to present the effectiveness of the appraisal system of a Multi national company in India. Hence, the performance appraisal system of this company was studied. The study also explains how performance appraisal systems have encouraged employee development in the organization considered.